The impact of age and maturation on physical performance capacities in emerging adolescent surfing athletes: An argument for off-water training - Perejmibida, A.; Conlon, J. A.; Lyons, M.; Cripps, A. (International Journal of Sports Science & Coaching, 2023)
Surfing is a high intensity intermittent sport, rapidly increasing in popularity in recent years. Surfing athletes who possess holistic physical performance capabilities, for example; strength, power, dynamic balance and flexibility, are better able to respond to the dynamic and variable nature of competition. Talent identification (TID) and long-term athlete development (LTAD) processes must consider the physical capacities necessary for performance and the impact of maturation. This study aimed to identify the physical performance capacities of state level adolescent surfers and explore their association with age and maturation. Participants (13.68 ± 1.57 years, 159.54 ± 12.33 cm, 50.07 ± 12.25 kg) were recruited from the Surfing Western Australia (WA) High Performance Pathway (HPP). Athletes completed a TID testing battery including anthropometrics (height, sitting height, body mass, arm span, sum of 7 skinfolds), flexibility (sit and reach), lower body power (vertical and broad jump) and strength (isometric mid-thigh pull; IMTP), dynamic balance (time to stabilisation; TTS) and sensorimotor ability and stability (Athletic Ability Assessment; AAA). Findings demonstrated whilst many physical performance capacities improved with advanced age and maturation, relative lower body strength, dynamic balance and several components of the AAA did not. Further, physical performance capacities were similarly associated with both maturity and age, except total AAA, which was significantly associated with maturation but not age. In conclusion, these data highlight inefficiencies in the current physical preparation of emerging adolescent state-level surfing athletes and highlight the need for a more robust training programme to maximise athletic potential, including structured off-water training.